2018
DOI: 10.1186/s13046-018-0918-9
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA AFAP1-AS1 acts as a competing endogenous RNA of miR-423-5p to facilitate nasopharyngeal carcinoma metastasis through regulating the Rho/Rac pathway

Abstract: BackgroundActin filament-associated protein 1 antisense RNA 1 (AFAP1-AS1), a long noncoding RNA, is significantly highly expressed and associated with metastasis and poor prognosis in many cancers, including nasopharyngeal carcinoma (NPC). In this study, we aim to identify the role of AFAP1-AS1 acting as an oncogenic lncRNA to promote NPC metastasis.MethodsThe role of AFAP1-AS1, miR-423-5p, and FOSL2 in NPC metastasis was investigated in vitro and in vivo. Bioinformatics analysis and luciferase activity assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 73 publications
5
105
0
Order By: Relevance
“…However, in recent years, various functions of lncRNAs have been identified, including participating in the autophagy pathway 2,3 , controlling cell differentiation 4 , and acting as competing endogenous RNAs (ceRNAs) for microRNAs 2,5 . The role of some lncRNAs as ceRNAs of miRNAs has been demonstrated in cancer metastasis and invasion [6][7][8][9] . For example, Lian et al reported that lncRNA AFAP1-AS1 acted as a ceRNA of miR-432-5p, to promote metastasis in nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, various functions of lncRNAs have been identified, including participating in the autophagy pathway 2,3 , controlling cell differentiation 4 , and acting as competing endogenous RNAs (ceRNAs) for microRNAs 2,5 . The role of some lncRNAs as ceRNAs of miRNAs has been demonstrated in cancer metastasis and invasion [6][7][8][9] . For example, Lian et al reported that lncRNA AFAP1-AS1 acted as a ceRNA of miR-432-5p, to promote metastasis in nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…One such recognized is lncRNA ZEB1-AS1, which epigenetically activates ZEB1 and promotes prostate cancer metastasis [33]. Previously, lncRNA AFAP1-AS1 was reported to act as a competing endogenous RNA of miR-423-5p to facilitate nasopharyngeal carcinoma metastasis [34]; while Yin et al demonstrated that AFAP1-AS1 is associated with poor survival of patients with non-small cell lung cancer, and enhances cell proliferation via inhibition of p21 expression [35]. Until now, the exact regulatory mechanism of AFAP1-AS1 in cancer progression and resistance is not defined.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumors are a major threat to human health. Nasopharyngeal carcinoma, oral cancer, thyroid cancer, ovarian cancer, and lung cancer are common malignant tumors that show high rates of metastasis . Moreover, the malignant progression and high mortality rates associated with these tumors are related to their insidious onset, frequent metastasis and recurrence, and poor prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma, oral cancer, thyroid cancer, ovarian cancer, and lung cancer are common malignant tumors that show high rates of metastasis. [26][27][28] Moreover, the malignant progression and high mortality rates associated with these tumors are related F I G U R E 2 circMAN1A2 was highly expressed in the sera of patients with oral cancer, thyroid cancer, ovarian cancer, or lung cancer. A-D, Relative expression of circMAN1A2 in oral cancer (A), thyroid cancer (B), ovarian cancer (C), and lung cancer (D).…”
Section: Discussionmentioning
confidence: 99%